A pilot study to compare the efficacy and safety of Betafoam® and Allevyn® Ag in the management of acute partial thickness burns. Issue 1 (January 2019) - Jeong, Cheol Soo; Kwak, Kyunghee; Hur, Jun; Kym, Dohern
Highlights: Betafoam® is a new polyurethane foam dressing containing 3% povidone-iodine. Betafoam® has comparable wound healing efficacy to Allevyn® Ag Gentle, with no notable safety concerns. The lower cost of Betafoam® may make it an attractive wound dressing option. Abstract: Betafoam® is a new polyurethane foam dressing containing 3% povidone-iodine. This pilot study aimed to assess the performance of Betafoam® for the management of acute partial thickness burn wounds, by comparing its efficacy and safety with those of a silver foam dressing, Allevyn® Ag Gentle. This randomized, two-arm, pilot study was conducted between June 2016 and February 2017 at 2 sites in the Republic of Korea. A total of 32 patients (aged ≥19 years) with acute partial thickness burn wounds and burn total body surface area ≤15% were randomized to treatment with Betafoam® or Allevyn® Ag Gentle dressings for 28 days. Endpoints included target lesion re-epithelialization, infection, pain, and adverse events. Mean time to complete re-epithelialization was similar in the Betafoam® and Allevyn® Ag Gentle groups (12.53 ± 1.13 vs 9.88 ± 1.02 days, P = 0.1556). All patients had complete re-epithelialization by day 28, and none had a burn wound infection during the study period. Analgesic use and patient-reported pain scores during dressing changes were not significantly different between dressing groups. No adverse events were associated with application of the dressings. The results of this first-in-human study suggest that Betafoam® has comparable wound healing efficacy to Allevyn® Ag Gentle, with no notable safety concerns.